Implementing Cooperative Learning To Enhsnce Students’ Interest In Reading Skill - Hanan, Ahmad; Tawali, Tawali (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aim of this study was to investigate how the implementation of cooperative learning strategies, particularly Numbered Heads Together (NHT), can enhance students' interest in reading comprehension. Classroom Action Research was employed as the research design, with data collection tools consisting of questionnaires and observations. The study focused on students from class VIII A at MTS Nurul Islam Sekarbela. Both qualitative and quantitative approaches were used for data analysis. The research comprised two cycles of Classroom Action Research involving 27 students. The findings revealed an improvement from cycle I to cycle II. In cycle I, four students achieved a very high percentage score, while 20 students attained a high percentage score and three students scored in the medium category. The results of cycle II were higher than those of cycle I. Based on the data, the research was deemed successful as it met the success criteria of achieving a minimum interest level of 61% in the high percentage category for students' comprehension. Observations indicated an improvement in the classroom environment, with students demonstrating increased interest, attentiveness to the teacher, enjoyment, and greater participation in learning activities. This suggests that cooperative learning strategies can indeed enhance students' interest in reading comprehension.